2007
DOI: 10.1159/000108431
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at the Osteoprotegerin and Interleukin-6 Genes in Relation to First-Ever Stroke

Abstract: Background: Arterial calcification and osteoporosis often coexist, especially in postmenopausal women. Osteoporosis associates with a substantially increased risk of stroke in elderly women, suggesting that impaired estrogen signaling may link stroke and osteoporosis. Osteoprotegerin (OPG, TNFRSF11B) and interleukin-6 (IL-6, IL6) are putative target genes for estrogen signaling and have been implicated in both cardiovascular diseases and osteoporosis. We hypothesized that specific polymorphisms in these genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 82 publications
0
14
1
2
Order By: Relevance
“…33 In another interesting study researchers assessed the potential role of estrogen signaling on this association through putative target genes (osteoprotegerin and interleukin-6); carriers of the osteoprotegerin-1181C/C genotype had a significantly increased risk of intracerebral hemorrhage (P=0.005). 34 This implies that alterations in osteoprotegerin-mediated signaling in the vasculature may be involved in the pathophysiology of hemorrhagic stroke. There have also been a number of studies on the effect of statins on bone mass.…”
Section: Strokementioning
confidence: 99%
“…33 In another interesting study researchers assessed the potential role of estrogen signaling on this association through putative target genes (osteoprotegerin and interleukin-6); carriers of the osteoprotegerin-1181C/C genotype had a significantly increased risk of intracerebral hemorrhage (P=0.005). 34 This implies that alterations in osteoprotegerin-mediated signaling in the vasculature may be involved in the pathophysiology of hemorrhagic stroke. There have also been a number of studies on the effect of statins on bone mass.…”
Section: Strokementioning
confidence: 99%
“…Previous investigations have demonstrated a significant association between the -174G/C (rs1800795) polymorphism and risk of ischemic stroke, but their results have been inconsistent (Lalouschek et al, 2006;Strand et al, 2007;Yang et al, 2014;Bazina et al, 2015). Bazina et al (2015) conducted a study with 144 ischemic stroke patients and 187 healthy controls, and identified a significant link between this polymorphism and an increased risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…2005; Strand et al. 2007), OPG also served as a vascular calcification inhibitor (Clancy et al. 2006).…”
Section: Discussionmentioning
confidence: 99%